The Cambridge Companion to Foucault - Gutting, Gary (Cambridge Cambridge University Press, 1994)
Michel Foucault was one of the most important contemporary French thinkers. He was of major significance as a philospher, historian, and social critic. This volume offers a systematic and comprehensive survey of his work through a set of specially commissioned essays. These essays provide an introduction to Foucault's major books, from his early work on madness through his history of sexuality, and relate his thought to major contemporary movements such as critical theory and feminism. This revised edition contains five new essays and an extensive, updated bibliography.
Keywords: Foucault, Michel -- 1926-1984; 20th Century (1901-2000); Philosophy; France